Challenges for agri-environmental policies in CEE Countries - Anett Zellei (Humboldt University of Berlin, Department of Agricultural Economics, Central and Eastern European Sustainable Agriculture International Research Project (CEESA), 2001)
All Central and Eastern European Countries (CEECs) have been going through a severe agricultural depression since their centrally planned economies collapsed in the early 1990s. It has now become clear that the transition process is far more complex and is likely to be much more protracted than was first expected. The agricultural policies of the Communist era resulted in considerable environmental problems, which are still present to varying degrees even after a considerable decrease in agricultural inputs during the past ten years. On the other hand, CEECs still retain a significant proportion of Europe? s biodiversity. The existing low input and low intensity agriculture practised in these countries can be perceived in certain respects as an opportunity for environmental sustainability in the agricultural sector. However, in view of future EU membership and accompanying policies, the question is to what extent the requirements of environmental protection and nature conservation will be taken into account in the CEECs? policy formation. The paper presents a preliminary survey of agri-environmental problems and relevant regulations in the Central and Eastern European Countries and identifies future challenges for their agri-environmental policy formation.
Keywords: 330; Agrarpolitik; Umweltpolitik; Osteuropa